Pre-surgical nasoalveolar moulding in cleft lip and palate patient: A case report - RAJ K, DR.SOUNDER; SRIVASTAVA, DR. RACHANA; GAUR, DR. SATYAM; GHOSH, DR. TUHINA (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Cleft lip and palate (CLP) is the most common congenital deformity of the oral cavity. Recently, nasoalveolar moulding (NAM) has evolved as a presurgical technique which reduces the severity of the oronasal defect. NAM improves the facial appearance and function by moulding the nasal cartilages, premaxilla, and the alveolar ridges before the corrective surgical procedures. Utilization of the NAM technique has eliminated the surgical scars associated with the traditional columella reconstruction and it has reduced the number and cost of the revision surgical procedures. NAM for CLP should be used after the birth and continued till further specific corrective surgeries are performed.